The Role of Videos in Enhancing English Language Skills: A Systematic Literature Review - Putri, Fathi Fajriani Putri; Winanda, Vivit Salsabila; Tarihoran, Naf’an (Jurnal Ilmu Sosial dan Humaniora, 2025)
With video-based learning being a major factor in improving English language proficiency, technology has emerged as a crucial tool in language instruction in the digital age. By combining visual, aural, and contextual components, videos offer a multimodal learning experience that improves speaking, listening, and comprehension skills. Despite these benefits, there are still issues with optimizing video-based learning outcomes and guaranteeing active learner engagement. The effectiveness of different video types—including instructional, conversational, interactive, and authentic content—in English language learning is investigated in this study by methodically reviewing the body of existing literature. We compiled the results of 21 studies published between 2021 and 2025 using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The studies were sourced from Google Books, ScienceDirect, Scopus, Mendeley, Taylor & Francis, and Google Scholar. The review identifies best practices for instructional design and interactivity while examining the effects of video-assisted learning on student motivation, engagement, and skill development.